BIMBINGAN DAN KONSELING ISLAM: METODOLOGI MENGHILANGKAN KETAKUTAN DAN KESEDIHAN DALAM PERSPEKTIF PSIKOLOGI DAN TAFSIR MAUDHŨĬ - Ichwansyah Tampubolon (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2020)
Psychology and the Al-Qur'an provide very important information about human psyche and also provide solutions for efforts to eliminate, especially, the problems of fear and sadness from human feelings. However, Psychology is more oriented to material-cognitive matters of human feelings, meanwhile Al-Qur'an puts forward aspects of divine spirituality and humanistic values. Unlike Psychology, Al-Qur'an also provides strategies and methods of counseling and therapy for humans by approaching oneself with Allah intrinsically and emphasizes the importance of efforts to attain the peak of good deeds socially and humanity. Al-Qur'an warns that humans can foster their emotional aspects psychologically and spiritually in order to produce good behavior to gain safety, benefit and happiness in this world and in the hereafter.